2019
DOI: 10.1039/c9se00102f
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite solar cell resilience to fast neutrons

Abstract: The high power-per-weight ratio displayed by metal-halide perovskite PVs is a key advantage of these promising devices for applications that require low payload, such as in space and avionics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 44 publications
(49 reference statements)
1
42
0
Order By: Relevance
“…Cacialli et al reported their study on fast neutron of PSCs. [46] The device showed the remarkable resilience against one of the most hazardous forms of radiation. Fast neutrons lead to permanent effects likely originating from atomic displacement in the active material.…”
Section: Other Rays and High-energy Particles Resistancementioning
confidence: 99%
“…Cacialli et al reported their study on fast neutron of PSCs. [46] The device showed the remarkable resilience against one of the most hazardous forms of radiation. Fast neutrons lead to permanent effects likely originating from atomic displacement in the active material.…”
Section: Other Rays and High-energy Particles Resistancementioning
confidence: 99%
“…Among these, the p–i–n type cells have the advantages of low processing temperature, low hysteresis, [ 8 ] high performance at low operation temperature, [ 6 ] and are considered as a good candidate for space applications. [ 9–11 ]…”
Section: Introductionmentioning
confidence: 99%
“…The power conversion efficiency (PCE) dropped with 36% after the balloon flight. [ 11 ] Several accelerated tests exposing the solar cells to high doses of high energy radiation using electrons, [ 12 ] protons, [ 13,14 ] neutrons, [ 15 ] and gamma‐rays [ 16 ] have also been performed in PSCs. In all but one case, the initial PCE of the used cells was in between 5% and 14%, which may not be representative as only high‐efficiency PSCs will eventually be used in space missions.…”
Section: Figurementioning
confidence: 99%